INVESTIGASI KINERJA ANTENA BERDASARKAN DISPERSI ANOMALI METAMATERIAL STRUKTUR HEKSAGONAL SPLIT RING RESONATOR - Yan Soerbakti; Romi Fadli Syahputra; Saktioto Saktioto; Moh. Danil Hendry Gamal (Komunikasi Fisika Indonesia, 2020)
Metamaterial (MTM) anomaly dispersion characteristics have a great interest to be analyzed in the potential for increasing antenna performance. Dispersion material with a simple structure is able to cover the weaknesses of the antenna parameters. Characterization and optimization need to be applied to the MTM antenna design to obtain more effective antenna performance. Antenna operation is performed at 0-9 GHz microwave frequency with four SRR-H MTM structures varying in three radii of 2.5 mm, 2.7 mm, and 2.9 mm. The highest MTM characteristics occurred at four SRR-H radii of 2.9 mm with a refractive index of -8.5 which resulted in antenna parameters RL -48.8 dB, 5.98 dBi, and working frequency of 1.09-9.00 GHz. Antenna radiation occurs precisely in all MTM structures with an isotropic pattern or in all directions of 4.63 dBi at a frequency of 5.976 GHz.